Scroll or Stuck: Uncovering Fear of Missing Out (FOMO) Among Public Relations Students - Anisa Oktafriani; Yanti Dwi Astuti (Master of Communication Science Program, Universitas Diponegoro, 2025)
This study aims to explore the lived experiences and meaning-making of FoMO among members of the PERHUMAS Muda Yogyakarta 2023 cohort, a public relations student organization that paradoxically possesses strategic communication awareness yet remains vulnerable to FoMO. Using a qualitative approach with Interpretative Phenomenological Analysis (IPA) and the Self-Determination Theory (SDT) framework, data were collected through in-depth interviews, observation, and documentation involving four informants. Findings reveal that FoMO is not merely a fear of missing out, but a manifestation of efforts to fulfill three basic psychological needs: (1) Autonomy, in which FoMO drives digital identity management strategies through account separation (first/second account); (2) Competence, in which FoMO acts as a double-edged catalyst, simultaneously triggering social comparison anxiety while driving productive behaviors such as participation in competitions; and (3) Relatedness, which creates a paradox of being